2018
DOI: 10.1093/cvr/cvy185
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific regulation of collagen I and III expression by 17β-Estradiol in cardiac fibroblasts: role of estrogen receptors

Abstract: The mechanism underlying the sex-specific regulation of collagen I and III in the heart appears to involve E2-mediated differential ERα and ERβ signaling in CFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 51 publications
3
65
0
Order By: Relevance
“…This allowed us to compare the effects of Fasudil and H1152P, to demonstrate the concentration-dependent effect of SR-3677, to confirm that ROCKs play a role downstream of TGF-β in cardiac fibroblasts behaviour as suggested before [10], and to validate the importance of ROCKdependent signalling events like the actin-MRTF-LOX regulation. In addition to the presented pharmacological study we have demonstrated in the past that ECT can be prepared from male and female cells to study sex-differences in cardiac fibrosis and from virally transduced cells allowing loss-and gain-of function studies [15,18,30,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed us to compare the effects of Fasudil and H1152P, to demonstrate the concentration-dependent effect of SR-3677, to confirm that ROCKs play a role downstream of TGF-β in cardiac fibroblasts behaviour as suggested before [10], and to validate the importance of ROCKdependent signalling events like the actin-MRTF-LOX regulation. In addition to the presented pharmacological study we have demonstrated in the past that ECT can be prepared from male and female cells to study sex-differences in cardiac fibrosis and from virally transduced cells allowing loss-and gain-of function studies [15,18,30,42].…”
Section: Discussionmentioning
confidence: 99%
“…We perform linear ultimate destructive tensile measurements in order to obtain information on tissue stiffness (Young's modulus, slope of the elastic region of the stress-strain curve) and on the strain to failure point reflecting the maximal extensibility of the tissue. We have previously demonstrated that this model is suitable to perform gain and loss of function experiments as well as small molecule studies [15,18,30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the estradiol could regulate ECM turnover by affecting the expression of MMP-2, which in turn is associated with altered ventricular remodeling in different cardiovascular pathologies (Dworatzek et al, 2019).…”
Section: Pro-fibrotic Triggersmentioning
confidence: 99%
“…However, this possible protective effect of oestrogens is lost with the lack of oestrogens after menopause, possibly leading to increased perivascular fibrosis and subsequent microvascular stiffening. Oestrogens also inhibit collagen I and III deposition through activation of oestrogen receptor (ER) α [30], while androgens such as testosterone promote the deposition of collagen via increasing TGF-β production [31]. This may also contribute to increased perivascular fibrosis in women after menopause.…”
Section: Structural and Functional Alterations In Microvascular Diseasementioning
confidence: 99%